2015
DOI: 10.1108/s1479-368720150000022006
|View full text |Cite
|
Sign up to set email alerts
|

Embodiment: A Multimodal International Teacher Education Pedagogy?

Abstract: (2016),"Blended learning for building student-teachers' capacity to learn and teach science-related interdisciplinary subjects: The case of Hong Kong", Asian Association of Open Universities Journal, Vol. 11 Iss 2 pp. 166-181 https://doi.org/10.1108/AAOUJ-09-2016-0029 Access to this document was granted through an Emerald subscription provided by All users group For AuthorsIf you would like to write for this, or any other Emerald publication, then pleas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…The body became a potent vehicle for reflection throughout the class as students began to realize that in preparing to become a teacher, they cannot separate, as one student reflected, their "own experiences and self from the act of teaching." In this sense, our students' experiences are similar to those of Forgasz's (2015) students for whom "[e]mbodiment offered a different way of accessing, and expressing, selfunderstanding" (p. 129) compared with the cognitive and discursive forms of reflective inquiry with which they were familiar.…”
Section: Learning Through the Bodymentioning
confidence: 66%
See 2 more Smart Citations
“…The body became a potent vehicle for reflection throughout the class as students began to realize that in preparing to become a teacher, they cannot separate, as one student reflected, their "own experiences and self from the act of teaching." In this sense, our students' experiences are similar to those of Forgasz's (2015) students for whom "[e]mbodiment offered a different way of accessing, and expressing, selfunderstanding" (p. 129) compared with the cognitive and discursive forms of reflective inquiry with which they were familiar.…”
Section: Learning Through the Bodymentioning
confidence: 66%
“…Although at times uncomfortable, their bodies became a powerful reflective tool for the preservice teachers, whether by enabling them to experience or access emotions, or by supporting them to uncover new meanings and deeper insights about themselves. Related to our students' experiences of their body's role in knowledge construction, these data largely reflect the kinds of ideas about the nature and value of embodied learning advanced by Nguyen and Larson (2015), Freiler (2008), and Forgasz (2014Forgasz ( , 2015.…”
Section: Learning Through the Bodymentioning
confidence: 84%
See 1 more Smart Citation
“…( [12], p. 53). Additionally, Forgasz in her exploration of embodied pedagogies in teacher education concluded that "hierarchical privileging of mind/intellect over body/emotion are deeply entrenched in the academy" ( [13], p.118).…”
Section: Embodimentmentioning
confidence: 99%
“…Drama is a subject and learning area whereby teaching and learning approaches are characterised by 'embodied' pedagogies (Bird and Sinclair, 2019;Forgasz, 2015), working collaboratively as a form of ensemble (Franks et al, 2014) and as a community (Munday and Fleming, 2016). Drama educator concerns for presence, embodiment and collective action are fundamental to their practice and the shift to online delivery meant embracing ways of working that challenged key foundations of their work and process.…”
Section: The Primacy Of the Embodied 'Face-to-face' Experiencementioning
confidence: 99%